Ultrassonografia Torácica no monitoramento de doença respiratória bovina em bezerras - Bárbara de Andrade Alves (2022)
Late or mistaken diagnoses are among the main obstacles to the control of the Bovine Respiratory Disease (BRD) complex in calves on-farm and establishing monitoring tools can be the key to overcome these problems. The objective of this study was to evaluate the prevalence, the moment of greatest risk for the occurrence and the evolution of respiratory disease in dairy calves through the detection and monitoring of lung lesions through thoracic ultrasonography (TUS). A total of 190 heifer calves from 7 to 180 days of age were evaluated using TUS, Wisconsin (WI) and California (CA) respiratory clinical scores, and pulmonary auscultation for the detection of BRD in a cross-sectional observational study; and 33 heifer calves were evaluated by the same methods weekly over 12 weeks from the second week of life in a longitudinal observational study. In the cross-sectional study, 17.89% (34/190) of the calves were observed with lung lesions identified via TUS. When comparing the other diagnostic methods used with the TUS, a reasonable agreement was observed between the TUS and the WI and CA scores, and a moderate agreement between the TUS and pulmonary auscultation. In the longitudinal study, of the 33 calves evaluated, 13 had lung lesions during the evaluation period. Of these, 11 showed resolution of the lesions after treatment was implemented, with an average lesion duration of 5.8 days. The minimum age for the onset of lesions was 29 days. The results point to a greater ability to detect cases of pneumonia by TUS, in addition to pointing out the advantages of using the method for the epidemiological characterization of pneumonia cases on the farm, to assist in the continuous monitoring of respiratory diseases and to evaluate the effectiveness of treatments implemented. However, thoracic ultrasonography has limitations that can and should be compensated by other diagnostic methods and it must be associated with efficient screening methods.